Pengaruh Lokasi,Harga dan Word of Mouth Terhadap Keputusan Pembelian pada Pesenjama Coffee Medan - Nurhasanah Putri; Roni, Shofan (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to determine the influence of location, price, and Word of mouth on purchasing decisions at Pesenjama Coffee Medan. The background of this research is based on the increasingly intense competition in the culinary business, particularly in the Marelan Raya area, as well as the decline in Pesenjama Coffee’s sales during the 2020–2024 period. This research uses a quantitative method with an associative approach. The population consists of all Pesenjama Coffee consumers, while the sample was determined using data were collected through questionnaires and analyzed using multiple linear regression with The assistance of SPSS.The results indicate that partially, the location variable has a positive and significant effect on purchasing decisions. The price variable also has a positive and significant effect on purchasing decisions. Likewise, Word of Mouth has a positive and significant effect on purchasing decisions. Simultaneously, location, price, and Word of Mouth have a positive and significant influence on purchasing decisions at Pesenjama Coffee Medan.It can be concluded that consumer purchasing decisions at Pesenjama Coffee are strongly influenced by a strategic and accessible location, prices that are in line with quality and consumer purchasing power, as well as positive word of mouth formed through customer experiences. This research is expected to serve as an evaluation material for Pesenjama Coffee’s management in formulating more effective marketing strategies to increase consumer purchase intention.